A Novel Polymer Insect Repellent Conjugate for Extended Release and Decreased Skin Permeation of Para-Menthane-3,8-Diol - Sayyed I. Shah; Vitaliy V. Khutoryanskiy; Adrian C. Williams (MDPI AG, 2021)
Background: We developed a novel polymer insect repellent conjugate for extended release and decreased skin permeation of the volatile insect repellent p-menthane-3,8-diol (PMD). Methods: PMD was conjugated with acryloyl chloride via an ester bond to form acryloyl-PMD, which was subsequently copolymerised with acrylic acid at varying molar ratios. Copolymer structures were characterised by 1H NMR and FT-IR, analysed by thermogravimetric analysis (TGA), differential scanning calorimetry (DSC), molecular weights and reactivity ratios determined, and repellent loading assessed. Results: Using porcine liver esterases, ~45% of the insect repellent was released over five days. Penetration and permeation studies of the copolymer and free repellent using excised, full-thickness porcine ear skin showed no detectable permeation of the copolymer through skin compared to the PMD. Moreover, tape stripping revealed that over 90% of the copolymer remained on the outer surface of the skin, whereas free PMD was within all skin layers. A planarian toxicity fluorescence assay indicated that that the copolymer is unlikely to be a significant irritant when applied topically. Conclusions: this study demonstrates the feasibility of the copolymer approach to develop extended-release insect repellents while reducing skin uptake and transdermal permeation of the small-molecular-weight active ingredient, in order to minimise any adverse effects.